2020
DOI: 10.7759/cureus.10444
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Hand-Related Injuries at a Major Tertiary Care Burn and Reconstructive Center in Pakistan

Abstract: Bhatti et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…The majority experienced hand injuries, with ngers being the most common body part affected (67.5%) while (62.5%) also had fractured bones associated with their hand injuries. Higher OIs (82%) were seen in males compared to females (17%) which is a trend also re ected in international literature [14] Approximately one in ten (i.e., 446 000) youth are engaged in secondary vocational learning in Pakistan, with the majority being male (67%) learners [15]. Previous approaches to health surveys of youth have mainly focused on school-based youth as seen in the CDC's Global School-based Student Surveys (CDC-GSBHS).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The majority experienced hand injuries, with ngers being the most common body part affected (67.5%) while (62.5%) also had fractured bones associated with their hand injuries. Higher OIs (82%) were seen in males compared to females (17%) which is a trend also re ected in international literature [14] Approximately one in ten (i.e., 446 000) youth are engaged in secondary vocational learning in Pakistan, with the majority being male (67%) learners [15]. Previous approaches to health surveys of youth have mainly focused on school-based youth as seen in the CDC's Global School-based Student Surveys (CDC-GSBHS).…”
Section: Introductionsupporting
confidence: 76%
“…Occupational injuries (also known as work injuries (WIs)), which are injuries that occur at work or in relation to one's occupation, have been reported to be two times higher among young workers (16-19 years) compared to workers of older ages [13]. Although dedicated studies on OI in vocational youth from Pakistan are rare, one regional study [14] on OIs seen at an emergency department reported higher OIs (47%) among the younger workers (14-18 years) as compared to older workers(18-35 year) 25% from the Rawalpindi region [14]. The majority experienced hand injuries, with ngers being the most common body part affected (67.5%) while (62.5%) also had fractured bones associated with their hand injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic hand injuries are common worldwide, and most of the global burden of complex hand injuries requiring surgical intervention is shared by South and East Asia [ 1 ]. Most hand injuries are occupational, occur in the dominant hand, and result in fractures of small bones, tendon injuries, and soft tissue loss [ 2 , 3 ]. De-gloving hand injuries require coverage by fasciocutaneous flap.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational injuries (also known as work injuries (WIs)), which are injuries that occur at work or in relation to one's occupation, have been reported to be two times higher among young workers (16-19 years) compared to workers of older ages [12]. Although dedicated studies on OI in vocational youth from Pakistan are rare, one regional study [13] on OIs seen at an emergency department reported higher OIs (47%) among the younger workers (14-18 years) as compared to older workers(18-35 year) 25% from the Rawalpindi region [13]. The majority experienced hand injuries, with ngers being the most common body part affected (67.5%) while (62.5%) also had fractured bones associated with their hand injuries.…”
Section: Introductionmentioning
confidence: 99%